Effect of Cavitation with Vibration on the Powerhouse Structure of Bulb Turbines Installed in Hydropower Stations - Praveen S; Marimuthu S; Manivannan S; Daniel Das A; Gizachew Assefa Kerga (Advances in Materials Science and Engineering)
Hydro energy is one of the world’s most abundant and valuable renewable electricity sources. Hydropower is an important source since it is a clean, sustainable, and cost-effective source of energy. The most perilous characteristic that affects the performance of the hydraulic turbine and its allied parts is the cavitation phenomenon, which is clear as the increase of vapor bubbles in the liquid through any hydraulic turbine. Cavitation causes vibration, which is very harmful to turbine guide bearings and their supporting structures. Sometimes heavy vibration causes cracks in the civil structure of the powerhouse where the bulb turbines are installed. The performance of the bulb turbine and the stability of the powerhouse structure are studied with the effect of cavitation, vibration, and deformation of the turbine casing. Experimental measurements are used to determine at what force the shape of cavitation is very destructive and crucial when the local pressure is less than the vapor pressure of the flowing water, at which static pressure cavities begin to breed and ruin. This paper focuses on small hydropower stations with bulb turbine installations, which emphasized the performance improvement of these turbines by avoiding cavitation on the runner blades. Allowing some cavitation on these machines is also recommended, which is within repairable condition, and the cavitation pitting can be repaired during annual maintenance.